Utilization of Trygon walga (Sting ray) from the Arabian Sea - A., Lekshmy Nair; K., Gopakumar (Fishery Technology, 2025)
Proximate composition and nutritive value of' iish powder prepared from Trygon walga caught fromthe off shore waters of the Arabian sea are reported. The fish powder has high protein and low fat content and is free from pathogenic organisms. PER of the fish powder is higher than that of' casein. It can be stored in sealed metallised poly- ester/LDPE pouches at am bient temperature for nine months without appreciable deterioration of quality.